Playgrounds as meeting places: Post-war experimentations and contemporary perspectives on the design of in-between areas in residential complexes - Resta, Giuseppe (2023)
Contemporary urban development has marginalised outdoor play areas, which still function as meeting places because they occupy a physical and socio-cultural dimension of in-betweenness. The text aims at revisiting the centrality of playgrounds in housing complexes, arguing that such areas should gain visibility in the contemporary discourse on public housing. This idea is underpinned by an examination of experimental projects carried out in the 1950s-70s by Lady Allen of Hurtwood, Riccardo Dalisi, Aldo van Eyck, and Group Ludic. They tested early forms of participatory design and community empowerment assuming the role of “aesthetic operators”. What can we learn from post-war playground projects? Building on their radical methodologies, we will discuss the fleeting nature of such experiments, how neglected neighbourhoods benefitted from playgrounds as meeting places, and contemporary perspectives that link children’s leisure space design with Living Lab ecosystems. Today, the artistic research of Céline Condorelli and Assemble collective shows how the playground is an essential tool for the imagination of the city of tomorrow.